2023
DOI: 10.1002/adfm.202305796
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Electron Transfer Toward On/Off Room Temperature Phosphorescence in Two Photochromic Coordination Polymers

Abstract: Photoswitchable room temperature phosphorescence (RTP) materials are of great interest due to their potential applications in optical devices and switches. Herein, two Zn‐based coordination polymers (CPs) (H3‐TPB)·[Zn6(H‐HEDP)(HEDP)3(H2O)2]·5H2O (complex 1; HEDP = hydroxyethylidene diphosphonate; TPB = 1,3,5‐tris(4‐pyridyl)benzene) and (H‐TPB)·[Zn3(H‐HEDP)(HEDP)(H2O)]·2H2O (complex 2) with distinguishable photochromism and tunable RTP are synthesized involving photoactive TPB molecules with different packing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…The measured proton conductivity of 1 at 70 °C is 1.71 × 10 –4 S·cm –1 (Table S10), which is about 3 times that with an initial low-temperature state, indicating the existence of an efficient proton transfer pathway in compound 1 . The conductivity values of compound 1 are similar to those of previously reported metal phosphonate compounds. , To further investigate the conduction mechanism of solid 1 , the activation energy ( E a ) was obtained according to the Arrhenius equation σ ( T ) = σ 0 exp­( E a / kT ), in which k (J·K –1 ) represents the Boltzmann constant and T (K) is the temperature. , The corresponding value with 0.2182 eV (Figure b) accords with the typical Grotthuss mechanism ( E a < 0.4 eV), implying proton hopping in the H-bonding network.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The measured proton conductivity of 1 at 70 °C is 1.71 × 10 –4 S·cm –1 (Table S10), which is about 3 times that with an initial low-temperature state, indicating the existence of an efficient proton transfer pathway in compound 1 . The conductivity values of compound 1 are similar to those of previously reported metal phosphonate compounds. , To further investigate the conduction mechanism of solid 1 , the activation energy ( E a ) was obtained according to the Arrhenius equation σ ( T ) = σ 0 exp­( E a / kT ), in which k (J·K –1 ) represents the Boltzmann constant and T (K) is the temperature. , The corresponding value with 0.2182 eV (Figure b) accords with the typical Grotthuss mechanism ( E a < 0.4 eV), implying proton hopping in the H-bonding network.…”
Section: Resultssupporting
confidence: 80%
“…The conductivity values of compound 1 are similar to those of previously reported metal phosphonate compounds. 46,47 To further investigate the conduction mechanism of solid 1, the activation energy (E a ) was obtained according to the Arrhenius equation σ(T) = σ 0 exp(E a /kT), in which k (J•K −1 ) represents the Boltzmann constant and T (K) is the temperature. 14,53 The corresponding value with 0.2182 eV (Figure 4b) accords with the typical Grotthuss mechanism (E a < 0.4 eV), implying proton hopping in the H-bonding network.…”
Section: Crystal Structure Of [Dy(h-hedp) 2 ]•H 3 -Tpi•4h 2 O (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoluminescence (PL) properties of hybrid materials have attracted increasing attentions because of their application potential in solid state lighting, anti-counterfeiting, etc. 12,28–32 The PL emissions of hybrid materials are always required to be regulated to cater for different requirements. 33–39 Several approaches are effective to tune the PL emissions, which includes altering the emission center, 40,41 functionalization, 42,43 variation of excitation light 44,45 and lattice defect engineering.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the rigid matrix and strong coordination interactions between metal ions/clusters and photoactive ligands can tightly fix the molecules, confining their motions/vibrations and promoting the generation of triplet excitons for efficient room temperature phosphorescence (RTP) emission . More importantly, their topological diversity, abundant host–guest systems, and hybrids with various materials (such as quantum dots, polymers, metal nanoparticles) endow MOFs as a highly versatile and tunable platform for exploring of multifunctional RTP materials . Despite promising results recently achieved on RTP materials, the design principle and construction method for the guidance of MOFs based RTP still remain unclear.…”
mentioning
confidence: 99%